Reflection seismic imaging in the Skellefte ore district, northern Sweden - Dehghannejad, Mahdieh; Juhlin, Christopher; Malehmir, Alireza; Juanatey, Maria A. Garcia; Skyttä, Pietari; Bauer, Tobias; Weihed, Pär (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2013)
Godkänd; 2013; 20131012 (pawe)